Strategi Harga Dan Promosi Dalam Meningkatkan Pembelian Pada Masa Pandemi Covid 19 - Noga Riza Faisol (Lembaga Pusat Penelitian dan Pengabdian kepada Masyarakat (LP2M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
We can see the rapid development of the business in the field of motorcycle sales with the many motorcycle dealers or showrooms that have been established. The rapid progress of motorcycle sales activities can lead to a level of intense business competition. Likewise for motorcycle showrooms that sell similar goods. With the existence of similar products sold by different dealers or showroom businesses for buying and selling used motorcycles, while the diverse desires of consumers make consumers free to choose products that can satisfy their needs. The focus of this research is what is the price strategy and what is the promotion strategy at the Suwarno motorbike showroom in Maesan during the Covid 19 pandemic? The aim of the study was to find out the promotional price strategy at the Suwarno Motor Showroom in Maesan during the Covid 19 pandemic. This research uses a qualitative approach and the type of research is a case study. The results of this study are 1. The Suwarno Motor Maesan Showroom in setting prices also provides promos for each motorbike credit by obtaining helmets for consumers who credit motorbikes. 2. The promotion strategy used by the Suwarno motor Maesan showroom is using radio and Facebook media advertising. They announce via radio when there is a promo